PENGARUH EARNINGS MANAGEMENT DAN MEKANISME CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SERTA IMPLIKASINYA TERHADAP RETURN SAHAM - Sari, Inayah Adi; Haryanti, Anies Indah (PERMANA, 2012)
This study aims to analyze the effect of earnings management and corporate governance mechanisms on the disclosure of corporate social responsibility and its implications for stock returns. The population in this study was a manufacturing company listed on the Indonesia Stock Exchange. The scope of its activities is to engage in the fishery. Samples used in this study were as many as 3 companies. Independent variable used in this study were earnings management and corporate governance mechanisms that be delegated by the composition of the board of independent directors, institutional ownership, and audit committees. While the dependent variable was stock returns. Corporate social responsibility disclosure as an intervening variable while firm size and leverage as control variables. Based on the results of multiple linear regression analysis, the study concluded that the composition of the board of independent directors and institutional ownership were not significantly positive effect, the audit committee and firm size have significant positive effect, while earnings management and leverage were significantly negative effect on the disclosure of corporate social responsibility. In addition, the research found that the disclosure of corporate social responsibility was not significantly positive effect on investor reaction was reflected in stock returns. Keyword: earnings management, corporate governance, corporate social responsibility, stock returns.